Impact of systemic lupus erythematosus on adverse outcomes and readmission after total shoulder arthroplasty: a Nationwide Readmission Database analysis 2016–2020 - Hao-Ming Chang; Tzu-Hao Wang (Journal of Orthopaedics and Traumatology)
Abstract Background The impact of systemic lupus erythematosus (SLE) on total shoulder arthroplasty (TSA) outcomes is unclear. This study investigated the association between SLE and short-term TSA outcomes. Methods Data from the Nationwide Readmission Database (NRD) 2016–2020 of patients ≥ 20 years old who underwent primary TSA were included. SLE was identified by International Classification of Diseases, Tenth Revision, and Clinical Modification (ICD-10-CM) codes. Outcomes were compared between patients with and without SLE, and propensity-score matching based on age and sex was performed. Results This study included 1960 matched TSA patients (980 with SLE and 980 without SLE). The mean patient age was 65.7 years, and 92% were female. After adjusting for covariates, SLE was significantly associated with a higher risk of surgical complications (odds ratio [OR] = 1.48, 95% confidence interval [CI]: 1.13–1.93), acute postoperative hemorrhagic anemia (OR = 1.48, 95% CI 1.05–2.09), and increased 30-day (OR = 2.11, 95% CI 1.30–3.40) and 90-day (OR = 1.59, 95% CI 1.11–2.26) readmission rates. Patients with SLE with Charlson Comorbidity Index scores of 0 or > 1 had a significantly higher 90-day readmission rate (OR = 2.45 and 1.48, respectively). Additionally, patients with SLE ≥ 65 years old had a significantly higher risk of complications (OR = 1.56). Patients with SLE undergoing reverse TSA also exhibited a significantly increased 90-day readmission risk (OR = 1.71). Conclusions SLE significantly increases the risk of postoperative complications and readmissions following TSA, especially in older patients and those undergoing reverse TSA. However, the lack of data on immunosuppressive therapy, laboratory tests, and disease activity may weaken the strength of the evidence.